Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.4321/s1130-01082010000500003
|View full text |Cite
|
Sign up to set email alerts
|

Dilated intercellular spaces in subtypes of gastroesophagic reflux disease

Abstract: Background: dilatation of the intercellular spaces by electron microscopy has been considered as an early morphological marker of tissue injury in gastroesophageal reflux disease. The degree of dilatation in Barrett's esophagus is currently unknown.Objectives: to determine the frequency of dilated intercellular spaces in Barrett's esophagus.Material and methods: cross-sectional and prospective analysis of consecutive patients with gastroesophageal reflux disease. We selected symptomatic patients > 18 years and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
12
1
1
Order By: Relevance
“…This finding could also explain why patients with BE have fewer symptoms compared to patients with GERD [27]. Nevertheless, our results are in contrast to one recently published study by Alvaro-Villegas and coworkers who evaluated the dilation of ICS by electron microscopy in patients with BE, NERD, ERD, and healthy controls [32]. They found that the dilation of ICS was increasingly greater from NERD to BE and higher in biopsies taken at 5 cm than at 2 cm of the squamous columnar junction.…”
Section: Discussioncontrasting
confidence: 85%
“…This finding could also explain why patients with BE have fewer symptoms compared to patients with GERD [27]. Nevertheless, our results are in contrast to one recently published study by Alvaro-Villegas and coworkers who evaluated the dilation of ICS by electron microscopy in patients with BE, NERD, ERD, and healthy controls [32]. They found that the dilation of ICS was increasingly greater from NERD to BE and higher in biopsies taken at 5 cm than at 2 cm of the squamous columnar junction.…”
Section: Discussioncontrasting
confidence: 85%
“…On the other hand, Barrett's esophagus (BE), an end of the spectrum of GERD, may also be of interest in the ultramicroscopic view. From an electron microscopic investigation, BE was revealed to have a greater DIS compared to NERD or erosive esophagitis [18]. This study did not specifically discern the subdivided epithelial layer, and our result may be of note for investigating strata change seen on BE tissues.…”
Section: Discussionmentioning
confidence: 87%
“…Nonetheless, Barrett's has been produced in a rat model of reflux, is more commonly found in GERD than in healthy subjects and is reported to appear in those with erosive esophagitis that did not initially have Barrett's esophagus(73-75). Moreover, there is evidence that NERD, erosive esophagitis and Barrett's esophagus share a common histopathologic feature within esophageal (squamous) epithelium, that is DIS(34, 76). Since DIS is a reflection of a break in barrier function, it supports the concept that these three forms of GERD share a common pathogenesis (see Figure 2).…”
Section: Endoscopic Types In Gerdmentioning
confidence: 99%